SUMBER MAKNA HIDUP NELAYAN PANTAI MENGANTI: Studi Interpretative Phenomenological Approach (IPA) - Emil Niti Kusuma (Department of Islamic Psychology, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
The aim of this study is to reveal what are the sources of meaning of life and what are the characteristics of meaning of life. The study was conducted on the subject of five fishermen in Menganti Beach, Kebumen, Central Java. This study imprints the phenomenology paradigm, especially the Interpretative Phenomenological Approach (IPA) which is useful to uncover the meaning of life of the fishermen. The findings in this study include: 1) sources of fishermen's life meaning that are structured in the form of creative values ​​(such as self-actualization, and structuring of the meaning of life), attitudinal values ​​(attitudes facing boundary situations, self-control, fortitude, courage), experiential values ​​( vertical self- transcendence, horizontal self-transcendence, related and well-being); 2) characteristics of the meaning of life of fishermen consisting of unique experiences, concrete results, meaning of life as a guide to direct life forward.